Effect of heat treatment on the spectroscopic properties of tellurite glass - S.F. Yuhari; Asmahani Awang; M.A.A. Rajak; Jedol Dayou (Faculty of Science and Natural Resources, 2020)
This study reports the spectroscopic properties of tellurite glass with composition of 70TeO220ZnO9.5Na2O0.5Er2O3 synthesized using melt-quenching technique. The spectroscopic properties of glasses with heat treatment at varying temperature are found to vary due to the structural changes. The DTA spectra of TZNE glass evidenced the glass transition temperature (Tg), onset crystallization temperature (Tx) and glass crystallization temperature (TC1 and TC2) located at 79 °C, 307 °C, 435 °C and 696 °C, respectively. The FTIR spectra were recorded at room temperature shows the significant peaks positioned at 493 cm-1 , 559 cm-1 , 678 cm-1 , 2184 cm-1 , 2332 cm-1 and 3795 cm